THE PERUVIAN CIVIL CODE... THIRTY YEARS LATER. LIGHTS AND SHADOWS ON THE HOME - Cabrejo Ormachea, Napoleón (2015)
In the Peruvian legal world is commonly thought that the Civil Law changes slower than the criminal law or commercial law, and that after the Peruvian Constitution, the Civil Code is the highest legislative body of our nation state. Today, thirty years of his term as a civil regulatory framework, we can be certain of that assertion. However, in some areas such as home, the change has been made faster. However lights for some time brought the then brand-new Civil Code on this matter, it soon would rise on some shadows contrast with the concepts of domicile introduced by a new constitution which came into force with great vigor. Thus, thirty years after the enactment of the Civil Code, between light and shadow, yet we continue to reflect on this important legal concept born of ancient Rome.